2006
DOI: 10.1016/j.jbiomech.2005.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of microdamage formation using a mineral-collagen composite model of bone

Abstract: Age-related changes in bone quality are mainly manifested in the reduced toughness. Since the postyield deformation of bone is realized through microdamage formation (e.g., microcracking and diffuse damage), it is necessary to understand the mechanism of microdamage formation in bone in order to elucidate underlying mechanisms of age-related bone fractures. In this study, a twodimensional shear lag model was developed to predict stress concentration fields around an initial crack in a mineral-collagen composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…We present a mechanistic model for bone fibril deformation and failure including details of collagen deformation, collagen-mineral interaction and mineral fracture. Past related models (Akkus, 2005, Hellmich et al, 2004Fritsch and Hellmich, 2007;Ja¨ger and Fratzl, 2000;Kotha and Guzelsu, 2003;Wang and Qian, 2006;Arnoux et al, 2002;Ji and Gao, 2004) had considered collagen as a homogeneous continuum. Here an enhanced continuum model is employed allowing for sliding between collagen molecules, mineral-collagen interface debonding and mineral fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We present a mechanistic model for bone fibril deformation and failure including details of collagen deformation, collagen-mineral interaction and mineral fracture. Past related models (Akkus, 2005, Hellmich et al, 2004Fritsch and Hellmich, 2007;Ja¨ger and Fratzl, 2000;Kotha and Guzelsu, 2003;Wang and Qian, 2006;Arnoux et al, 2002;Ji and Gao, 2004) had considered collagen as a homogeneous continuum. Here an enhanced continuum model is employed allowing for sliding between collagen molecules, mineral-collagen interface debonding and mineral fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In Kotha and Guzelsu (2003), a yield condition for the collagen phase was included. Wang and Qian (2006) showed that increased non-enzymatic glycation reduces the collagen nonlinearity and makes crack coalescence more likely by allowing stress concentrations to develop around existing cracks. In combination this would make the tissue more brittle, and accelerate fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies from human and animal specimens, however, demonstrate that AGEs crosslinks are a determinant of bone strength, particularly postyield properties and toughness [66,68,78,98,122]. Such deteriorated bone mechanical properties induced by cross-link alteration has been shown to correlate with deformation and damage of bone [123] and microdamage accumulation [76]. There is a limitation in these studies as almost all studies employed Pen content as a surrogate marker of AGEs formation.…”
Section: Cross-links and Bone Strengthmentioning
confidence: 99%
“…Wang & Qian [122] also used a shear-lag model of a mineral-collagen composite to predict stress concentrations around the initial crack to identify the mechanisms of microdamage formation in bone. The focus of their study was on age-related bone fracture mechanisms.…”
Section: Analytical Modelsmentioning
confidence: 99%